Sertões em movimento: o nacional popular e o contemporâneo em Deus e o diabo, Árido movie e Baile perfumado - Silva, Leandro de Jesus da (2015)
This dissertation presents a critical study on the movie “Black God, White Devil”(1964), by the filmmaker Glauber Rocha born in Bahia State, and the way it is approached in the contemporay sertanejo cinema, specifically in the movies “Árido Movie” and “Perfumed Ball” directed by Paulo Caldas and Lírio Ferreira, both from Pernambuco State. The research takes into consideration the context in which the movie “Black God, White Devil” was created, its esthetic and discursive basis, its proposal for a collective popular memory revival focusing on the facts intrinsic to life in Canudos backlands, especially the cangaço (social banditry) and messianism and the clash the movie shows between the people’s version about these facts and the version found in official history books. It discusses how the speakability and visibility of an insular , mythical and sacralized sertão as the epicenter of a national identity and liberating revolt found in “Black God, White Devil” appear in the movies “Árido Movie” and “Perfumed Ball” in a roundabout way, which show asertão and a sertanejo torn between the dialogue with tradition and post-modernity.